Controls laboratory program with an accent on discovery learning. - Armstrong, Brian; Perez, Ronald
A sequence of laboratories is presented that have been designed to maximize student involvement in the design as well as execution of the laboratory exercises. The first lab begins with the simplest possible model, and students explore fundamental ideas of sensing, actuation, and feedback. With the second lab, student-designed experiments are introduced. By the end of the sequence, students independently design and implement system identification, controller design, and performance assessment for high performance tracking with a motor servo. The education literature establishes the potential for discovery learning to increase learning outcomes in laboratory teaching.
Keywords: controller design; controls laboratory; discovery learning; education; experiments; performance assessment; student-experiments.; system identification; teaching